(untitled) (Revista horizonte, 2016)
Objective: To determine the effect of a 12-week strength and power training plan in older women and to compare the results obtained in the maximum isometric strength of hand flexors. Materials and methods: Quasi-experimental - descriptive - randomized study. The sample consisted of 28 women with an average age of 66.6 Â± 8.44. The protocol for the determination of the physical performance characteristics were: maximum isometric strength of the right hand and maximum isometric strength of the left hand. The protocol for the anthropometric variables were age, weight, height and BMI. Statistical analysis: Standard statistical methods were used to calculate averages and standard deviations. Statistical significance will be accepted at p<0.05 for all analyses. All data were analyzed using the STATISTICA statistical package (Version 8.0, StatSoft, Inc, Tulsa, Oklahoma, USA). Results: The results of the present study demonstrate that a 12-week physical training program applied to older menopausal women does not increase the maximal isometric strength of right or left hand flexors. Conclusion: We conclude that the 12-week strength and power training plan has no significant effect on maximal isometric strength.